The Quest for a Truly Universal Influenza Vaccine - Jang, Yo Han; Seong, Baik Lin (Frontiers in Cellular and Infection Microbiology, 2019)
There is an unmet public health need for a universal influenza vaccine (UIV) to provide broad and durable protection from influenza virus infections. The identification of broadly protective antibodies and cross-reactive T cells directed to influenza viral targets present a promising prospect of developing a UIV. Multiple targets for cross-protection have been identified in the stalk and head of hemagglutinin (HA) to develop a UIV. Recently, neuraminidase (NA) has received significant attention as a critical component for increasing the breadth of protection. While the HA stalk-based approaches are taking the initiative through extensive animal studies, the correlates of cross-protection and vaccine safety in clinical stages are yet to be evaluated. Mucosal immune responses and cross-reactive T cell immunity across influenza A and B viruses intrinsic to live attenuated influenza vaccine (LAIV) has emerged as essential features to be incorporated into a UIV. Complementing the weakness of the stand-alone approaches, prime-boost vaccination combining HA stalk and LAIV is under clinical evaluation, with the aim to increase the efficacy and broaden the spectrum of protection. Preexisting immunity in humans established by prior exposure to influenza viruses may affect the hierarchy and magnitude of immune responses elicited by an influenza vaccine, limiting the interpretation of preclinical data based on naive animals, necessitating human challenge studies. A consensus is yet to be achieved on the spectrum of protection, efficacy, target population, and duration of protection to define a 'universal' vaccine. Moreover, safety concerns such as potential reversion into virulence for LAIVs and enhancement of disease by non-neutralizing or low-affinity neutralizing antibodies need to be addressed. This review discusses the recent advancements in the development of UIVs, rationales behind cross-protection and vaccine designs, and challenges faced in obtaining balanced protection potency, wide spectrum of protection, and safety relevant to UIVs.